Ekofeminisme - Candraningrum, Dewi
I. Dalam tafsir agama, pendidikan, ekonomi, dan budaya -- II. Narasi iman, mitos, air & tanah
Includes bibliographical references. - In Indonesian, with two articles in English
Keywords: Konferenzschrift